Home quarantine patient monitoring in the era of COVID-19 disease - Sicari, Sabrina; Rizzardi, Alessandra; Coen-Porisini, Alberto (Smart health (Amsterdam), 2022)
Patients' remote monitoring becomes even more crucial due to the spreading of the COVID-19 disease. Hospitals cannot accommodate all the patients who need to be taken care. Hence, tele-medicine or, as also named, tele-health, remains the only means available to keep the situation under control. In particular, it is important to monitor the patients who are subject to the home quarantine period. The reason is twofold: (i) their live status and symptoms must be controlled; (ii) they must not leave the permitted area during the quarantine period. To this end, the paper defines a set of rules and processes based on the Internet of Things (IoT) paradigm, which enable the integration of different devices, in order to monitor the required parameters related to the patient and notify life-threatening situations to the connected health-care structure. The conceived IoT network is developed by means of Node-RED, which is a flow-based programming tool targeted to the IoT. Particular attention is also paid to security and privacy requirements, since sensitive data related to the patients must be kept safe. The proposed solution is preliminary assessed by means of a test-bed.